1989
DOI: 10.1007/bf00610441
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses of photoresponsiveness in the Djungarian hamster,Phodopus sungorus

Abstract: Endotherms living at temperate and arctic latitudes must adjust their physiology and behavior in order to survive seasonal change. The Djungarian hamster uses photoperiod to cue annual cycles of reproduction and thermoregulation, and its responses to short photoperiod include loss of body weight and change in pelage color. Some individuals do not exhibit these responses when exposed to short days. In this study individual variation in photoresponsiveness is quantified, and four lines of evidence for a genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 25 publications
4
45
0
Order By: Relevance
“…A number of previous studies have shown body weight to be a poor predictor of sperm count [29], and photoperiod can affect body weight independently of testis size in rodents (e.g., [30,31]). Our previous work on F344 rats [18] showed similar qualitative results using adjusted or unadjusted measurements of testis size.…”
Section: Discussionmentioning
confidence: 98%
“…A number of previous studies have shown body weight to be a poor predictor of sperm count [29], and photoperiod can affect body weight independently of testis size in rodents (e.g., [30,31]). Our previous work on F344 rats [18] showed similar qualitative results using adjusted or unadjusted measurements of testis size.…”
Section: Discussionmentioning
confidence: 98%
“…This result contrasts with several studies concerned with the effects of environmental factors on reproductive processes, in which highly inbred hamsters or rats were subjected to experimentation (Blank 1992). In those studies, observed consistent physiological responses to manipulated conditions were due to the avoiding of among-animal variation that characterizes outbreeding stocks (Lynch et al 1989). Nonetheless, Horton and Rowsemitt (1992) emphasized the importance of individual variation in response to environmental information.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in reproductive photoresponsiveness can be seen among species, among geographical populations of the same species, ad even among individuals of the same geographical population (reviewed by [1]). In the latter regard, it has been shown now in laboratory stocks of Peromyscus, Microtus, Clethrionomys, Phodopus, and even in the highly domesticated Mesocricetus that some individuals undergo total reproductive regression when maintained on short day lengths, while other individuals of the same stock and species remain reproductively functional, and still others show intermediate levels of responsiveness (e.g., [2][3][4][5][6][7][8]). Selection experiments have established that at least some of this individual variation is genetically based [5,7,9,10].…”
Section: Introductionmentioning
confidence: 99%